DECRIMINALIZING MARIJUANA: UNDERSTANDING MARIJUANA DEBATE THROUGH HISTORY AND POLICY - Odabasi, Mehmet (European Scientific Journal, ESJ, 2014)
The globalization of the world by easy transportation and communication enabled the distribution of drugs to anywhere in the world. Among many drugs, marijuana has an exceptional place with being the most abused drug in many countries such as the United States of America and the United Kingdom. Particularly, marijuana use is prevalent among young people in the United States. Although 1970 Control Substances Act listed marijuana as a Schedule 1 drug, many states in the US have been enacting state legislatures on legalizing marijuana at least in terms of medical use. This paper examines marijuana in a comprehensive way by detailing marijuana facts, history, policy, and alleged medical usefulness in order to shed a light in understanding whether medical marijuana use should be decriminalized.